HUBUNGAN ANTARA USIA, STATUS GIZI, MOTIVASI KERJA, DAN PENGALAMAN KERJA DENGAN PRODUKTIVITAS KERJA OPERATOR BAGIAN PERAKITAN DI PT. X - Brigita Novianti; Bina Kurniawan; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
National automotive industry is now experiencing a very significant growth. Each company always attampt their workers to achieve a maximum wok productivity. Productivity can be influenced by age, nutritional status, work motivation and work experience. The purpose of this research was to analyze the correlation between age, nutritional status, work motivation and work experience with work productivity. Dependent variable in this research was work productivity and independent variables were age, nutritional status, work motivation and work experience. This was an explanatory research with cross sectional design. Population of this research were assembly parts operator with the total of 45 people and sampling technique was using simple random sampling. Data was collected using questionnaire and measurement of Basal Metabolic Rate (BMR). Data was analyzed using Rank Spearman correlation trial. Statistical results showed that there were correlation between age (sig = 0,000), nutritional status (sig = 0,000), work motivation (sig = 0,033), and work experience (sig = 0,028) with work productivity of assembly parts operator. Company should move the old operator to the wheel assembling or delivery and supply section, collaborated with company’s clinic to give socialization about nutritional needs and good nutritional intake to the operator, proposed to cathering section to make lunch menu’s survey, and gave positive motivation.